AN ECONOMIC NON-PRODUCTIVE GROUP STRETCHED THROUGH THE VERTICAL GARDEN WITH WASTE PRODUCTS: In Pakis Village, Sawahan District, Surabaya City - Dwie Retna Suryaningsih; Erna Haryanti (Yayasan Education and Social Center, 2021)
Economically non-productive groups in Pakis Village, Sawahan Sub-district, Surabaya City who are the target of this Community Service activity are members of PKK RT 05 and RT 06 RW IX Dukuh Kupang Timur Surabaya. Transfer of Knowledge and technology to the target includes Extension and training activities: Entrepreneurship Training, Marketing technique training, Post-harvest management training, and Vertical Garden cultivation techniques training. The implementation of Community Service in Pakis Village, Sawahan District, Surabaya City uses the PRRA (Participatory Rapid Rural) and RRA (Rapid and Rural Appraisal) methods. This activity allows targets to collaborate with universities as implementers on activities, including planning, organizing, implementing, and evaluating them. Increased motivation for independent entrepreneurship through vegetable cultivation activities, mastery of Vertical Garden technology effectively and efficiently, knowledge of post-harvest, packaging, and labeling technology can add value to vegetable products, and development of this activity as a sustainable entrepreneurial accomplishment this activity